2017
DOI: 10.1002/bjs.10476
|View full text |Cite
|
Sign up to set email alerts
|

Methodological overview of systematic reviews to establish the evidence base for emergency general surgery

Abstract: BackgroundThe evidence for treatment decision‐making in emergency general surgery has not been summarized previously. The aim of this overview was to review the quantity and quality of systematic review evidence for the most common emergency surgical conditions.MethodsSystematic reviews of the most common conditions requiring unplanned admission and treatment managed by general surgeons were eligible for inclusion. The Centre for Reviews and Dissemination databases were searched to April 2014. The number and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…High or unclear risk of bias within reviews have affected the conclusions drawn from this evidence synthesis. In a systematic review of 106 emergency surgery systematic reviews, a low risk of bias was found in 53.8%, identifying a common problem of poor quality reviews conducted in emergency surgery 50…”
Section: Discussionmentioning
confidence: 99%
“…High or unclear risk of bias within reviews have affected the conclusions drawn from this evidence synthesis. In a systematic review of 106 emergency surgery systematic reviews, a low risk of bias was found in 53.8%, identifying a common problem of poor quality reviews conducted in emergency surgery 50…”
Section: Discussionmentioning
confidence: 99%
“…The quality of randomised data and outcomes reporting in ASBO is limited [ 7 , 8 , 9 ]. The most recent trials in ASBO focus on the use of water soluble contrast agents [ 10 ], or laparoscopic surgery [ 11 ].…”
Section: Introductionmentioning
confidence: 99%